2009
DOI: 10.1002/lary.20187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic transplantation of adipose tissue‐derived stem cells on olfactory epithelium regeneration

Abstract: Our findings suggest the feasibility of ADSC transplantation as a treatment for head trauma-related olfactory dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Compared to the control group, the BMSC transplantation group had increased NGF expression. The expression began to increase 1 week after transplantation and peaked 3-5 weeks after transplantation [15,18,19]. As in our assessment system, measuring the thickness of the epithelium and performing nerve sheath analysis seem reasonable.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to the control group, the BMSC transplantation group had increased NGF expression. The expression began to increase 1 week after transplantation and peaked 3-5 weeks after transplantation [15,18,19]. As in our assessment system, measuring the thickness of the epithelium and performing nerve sheath analysis seem reasonable.…”
Section: Discussionmentioning
confidence: 96%
“…Human cord blood CD133-positive stem cells were intravenously injected to nod-scid mice and this was shown to provide conditions for regeneration of the olfactory neuroepithelium after permanent damage was induced by dichlobenil (16). Adipose tissue-derived stem cells were also intravenously injected to rats after their olfactory nerve was transected (17). However, the olfactory nerve transaction model is less likely to be appropriate for stem cell research.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in rat [70] , pig [71] and human models [72] have demonstrated the multipotentiality of head and neck-derived ASC.…”
Section: Profile and Identitymentioning
confidence: 99%
“…In another study, Kim et al showed the potential application of neckderived ASC for the treatment of head trauma-related olfactory dysfunction in terms of regeneration epithelium [70] . Olfactory epithelial degeneration was first induced in a rat model through unilateral transection of the olfactory nerve; regeneration of olfactory epithelium was then observed following systemic transplantation of neck-derived ASC [70] .…”
Section: Profile and Identitymentioning
confidence: 99%
See 1 more Smart Citation